The Brand Product of Polish Health Resort Tourism. Theoretical Assumptions and the Practice of Creating This Product with the Example of Selected Health Resort Communities - Bajon , Paweł (Studia Oeconomica Posnaniensia, 2018)
After the period of political and economic transformation health-resort municipalities in Poland have organize their development activities better and better. They care for their multidirectional development, thus responding consciously and purposefully to the requirements of sustainable development principles, changing and growing customer requirements, as well as competition within the sector on the domestic (between municipalities and companies) and the international arena. The postulate of building a brand health or health-resort/spa tourism product is accepted as a necessity and a natural process. The aim of the study is to analyze how selected health-resort communes determine their predispositions and development directions and how they try to determine their brand. The analysis proves rather an individual approach - the municipalities independently, or rarely in small relationships, develop their product concepts, are aware of market competition, and that their efforts in this competition are building an increasingly better image of health resort tourism as a whole. Concerned municipalities are Ciechocinek, Inowrocław and Uniejów.